Teaching english to a student with mild intellectual disability - Cepeda Calero, Jessica Lisbeth (2023)
The main objective of this qualitative research was to analyze the teaching and learning experiences of a pre-service English teacher and a student with a mild intellectual disability with the Total Physical Response and the Natural Approach in the context of remedial teaching in a private urban school in Salcedo-Cotopaxi during the 2022-2023 academic year. This study was applied using the action research method, which involved: problem identification, planning, implementation, and reflection (Atweh, et.al, 1998). The data was collected by using the teacher’s diary, student survey, and observation file. The principal findings regarding the teaching experiences with Total Physical Response and the Natural Approach had positive and negative aspects. The Total Physical Response method had successful results because the pre-service teacher was able to plan and teach her lessons and also, the use of body movements and mimics was favorable because the student felt comfortable learning. On the other hand, the application of the natural method was a little difficult because the pre-service teacher had many problems during the planning and class implementation. Consequently, the student presented difficulties in comprehension and language production. Finally, these findings suggest the integration of these methods in the teaching-learning of students with mild intellectual disabilities for a better learning experience.